1999
DOI: 10.1128/jvi.73.9.7607-7618.1999
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Recombination Demonstrates that the Spike Gene of Transmissible Gastroenteritis Coronavirus Is a Determinant of Its Enteric Tropism and Virulence

Abstract: Targeted recombination within the S (spike) gene of transmissible gastroenteritis coronavirus (TGEV) was promoted by passage of helper respiratory virus isolates in cells transfected with a TGEV-derived defective minigenome carrying the S gene from an enteric isolate. The minigenome was efficiently replicated in trans and packaged by the helper virus, leading to the formation of true recombinant and pseudorecombinant viruses containing the S proteins of both enteric and respiratory TGEV strains in their envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
226
0
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(236 citation statements)
references
References 59 publications
6
226
0
4
Order By: Relevance
“…5 Differences in virulence of mice coronaviruses have also been linked to genetic variance in the S protein. 6,7 and the serological response in the host is typically raised against the S protein. 8 However, the S, M, and N mature proteins all contribute to generating the host immune response as seen in transmissible gastroenteritis coronavirus, 9 infectious bronchitis virus, 10,11 pig respiratory coronavirus, 12 and mouse hepatitis virus.…”
Section: Introductionmentioning
confidence: 99%
“…5 Differences in virulence of mice coronaviruses have also been linked to genetic variance in the S protein. 6,7 and the serological response in the host is typically raised against the S protein. 8 However, the S, M, and N mature proteins all contribute to generating the host immune response as seen in transmissible gastroenteritis coronavirus, 9 infectious bronchitis virus, 10,11 pig respiratory coronavirus, 12 and mouse hepatitis virus.…”
Section: Introductionmentioning
confidence: 99%
“…Using a reverse genetics system, the S glycoproteins for a group 2 coronavirus (MHV), a group 1 coronavirus (TGEV) and a group 3 coronavirus (IBV) were demonstrated to be involved in the tropism of these coronaviruses [26][27][28][29][30]68,70]. For the TGEV, several amino acid changes at the Nterminus of the S protein resulted in the loss of enteric tropism [29,30]. In this study, an amino acid substitution was found at residue 581 (Leu → Phe) between P70 and P110; however, loss of kidney tropism of CK/CH/LHLJ/04V occurred between P40 and P70.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of S1 in determining cell and tissue tropism has been demonstrated for several coronaviruses, such as murine hepatitis virus [20][21][22][23][24][25][26][27][28], porcine transmissible gastroenteritis virus [29,30], and severe acute respiratory syndrome coronavirus [31]. In the case of IBV, the S1 subunit of the S protein determines the serotype of IBV and is responsible for viral attachment to cells.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus S protein is responsible for virus adsorption to susceptible cells through a specific virus-receptor interaction and induces membrane fusion between viral envelope and host cell membrane [5]. S protein is a main player for determining coronavirus tissue tropism, host specificity and viral pathogenicity [6][7][8][9][10][11][12]. Because most coronavirus neutralizing antibodies recognize S protein [1,13], it is not surprising that most of the current SCoV vaccine candidates are either the S protein subunit itself or those carrying S protein [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%